2016
DOI: 10.1007/s40279-016-0571-4
|View full text |Cite
|
Sign up to set email alerts
|

Creatine Supplementation and Upper Limb Strength Performance: A Systematic Review and Meta-Analysis

Abstract: Creatine supplementation is effective in upper limb strength performance for exercise with a duration of less than 3  min, independent of population characteristics, training protocols, and supplementary doses or duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 63 publications
4
66
0
8
Order By: Relevance
“…The elevated levels of muscle creatine were sustained in both cases with a maintenance dose of 2 g/day (30). Therefore, our results corroborate other findings (14,20,21,(31)(32)(33)(34)(35), i.e., low doses of creatine monohydrate supplementation, regardless of the use of saturation phase, could significantly increase maximum muscle strength and resistance to fatigue. Furthermore, no subjects in any of the groups reported any discomfort or side effects during the study period.…”
Section: Discussionsupporting
confidence: 90%
“…The elevated levels of muscle creatine were sustained in both cases with a maintenance dose of 2 g/day (30). Therefore, our results corroborate other findings (14,20,21,(31)(32)(33)(34)(35), i.e., low doses of creatine monohydrate supplementation, regardless of the use of saturation phase, could significantly increase maximum muscle strength and resistance to fatigue. Furthermore, no subjects in any of the groups reported any discomfort or side effects during the study period.…”
Section: Discussionsupporting
confidence: 90%
“…The MIP formulations included in 14 studies contained Cr, which has been shown to enhance upper 53 and lower body strength in several populations. 54 55 A recent meta-analysis 8 in >700 older adults found that Cr supplementation during RT Figure 4 Forest plot of the results from a random effects meta-analysis for multi-ingredient protein (MIP) supplementation compared with all non-MIP supplementation groups shown as mean difference with 95% CIs on one-repetition maximum lower body (kg) in young (<45 years) and old (>45 years) participants.…”
Section: Reviewmentioning
confidence: 99%
“…Creatine monohydrate (CM) supplementation increases muscle creatine and phosphocreatine stores, sustaining exercise that is otherwise limited by the inability of phosphocreatine resynthesis to keep pace with exercise fuel demands, for example, single and repeated bouts of high-intensity exercise (<150 s duration), with the most pronounced effects evident during tasks <30 s (Branch, 2003;Lanhers et al, 2017). Indeed, creatine supplementation received widespread attention in 1992 when the first report on successful loading protocols (Harris et al, 1992) was published at the same time as anecdotes emerged from the Barcelona Olympic Games regarding its use by gold-medal winning British track-and-field sprinters.…”
Section: Creatine Monohydratementioning
confidence: 99%